Інтеграція освітнього та науково-дослідного компонентів діяльності університетів Нідерландів - Заяць, Людмила (Studies in Comparative Education, 2013)
Статтю присвячено аналізу інтеграції освітнього та науково-дослідного компонентів діяльності університетів у Нідерландах. На основі вивчення нормативних документів Міністерства освіти, культури та науки Нідерландів, а також статистичних даних голландських наукових організацій автор окреслює основні наукові інституції країни, визначає роль та особливості університетської наукової діяльності, її тісний взаємозв’язок з освітньою функцією університетів, характеризує роль наукових організацій у процесі координації дослідницької діяльності різних установ. Статья посвящена характеристике интеграции образовательного и научно-исследовательского компонентов деятельности университетов Нидерландов. На основе анализа нормативных документов Министерства образования, культуры и науки Нидерландов, а также статистических данных голландских научных организаций автор определяет основные научные институции страны, определяет роль и особенности университетской научной деятельности, её тесную взаимосвязь с образовательной функцией университетов, характеризует роль научных организаций в процессе координации исследовательской деятельности разных учреждений. The article is devoted to the characteristic of the integration of the educational and research components of the Dutch universities. The author outlines the main scientific institutions, defines the role and peculiarities of the university research activities, its close connection with the educational function of the universities, describes the role of the scientific organisations in the coordination of various research establishments on the base of the analysis of the regulatory documents of the Ministry of Education, Culture and Science of the Netherlands and statistical data of the research organisations. The close relationship of the educational and research components of university activity is in the use of research results in the studying process, teaching orientation on the latest scientific advances and the active students involvement in the research activities. Having analyzed the organisation of the Netherlands scientific activity, author emphasizes the close cooperation between the universities and leading scientific and research organisations: The Netherlands Organisation for Scientific Research (NWO) and The Royal Netherlands Academy of Arts and Sciences (KNAW). They ensure rational distribution of funding, coordination of research activity in the country and facilitate to international cooperation. On the basis of the research author comes to the conclusion about advisability of the Netherlands successful experience use in the conditions of Ukrainian higher education reforming. In particular author emphasizes the following aspects: clear structure of the Netherlands university research activity; tight integration of research and educational components; priority of scientific research; government and public assistance represented by scientific organisations. All these aspects provide the high level of modern specialists training, who can constantly improve their skills.